Intrinsically bioactive cryogels based on platelet lysate nanocomposites for hemostasis applications. - Mendes, Bárbara Bruna da Silva (2020)
The currently used hemostatic agents are highly effective in stopping hemorrhages but have a limited role in the modulation of the wound-healing environment. Herein, we propose an intrinsically bioactive hemostatic cryogel based on platelet lysate (PL) and aldehyde-functionalized cellulose nanocrystals (a-CNCs). PL has attracted great attention as an inexpensive milieu of therapeutically relevant proteins; however, its application as a hemostatic agent exhibits serious constraints (e.g., structural integrity and short shelf-life). The incorporation of a-CNCs reinforced the low-strength PL matrix by covalent cross-linking its amine groups that exhibit an elastic interconnected porous network after full cryogelation. Upon blood immersion, the PL-CNC cryogels absorbed higher volumes of blood at a faster rate than commercial hemostatic porcine gelatin sponges. Simultaneously, the cryogels released biomolecules that increased stem cell proliferation, metabolic activity, and migration as well as downregulated the expression of markers of the fibrinolytic process. In an in vivo liver defect model, PL-CNC cryogels showed similar hemostatic performance in comparison with gelatin sponges and normal material-induced tissue response upon subcutaneous implantation. Overall, owing to their structure and bioactive composition, the proposed PL-CNC cryogels provide an alternative off-the-shelf hemostatic and antibacterial biomaterial with the potential to deliver therapeutically relevant proteins in situ.